Penerapan Platform Sistem Unggah Hitung Data Kinerja (SUHITA) Untuk Menunjang Kinerja Pemerintah Berbasis Teknologi Inovasi di Kabupaten Mojokerto - Dewantari, Dewantari; Fanida, Eva Hany (Universitas Negeri Surabaya, 2024)
The implementation of a performance management system allows government organizations to manage employee performance from the planning, monitoring, to performance evaluation stages in an accountable and transparent manner. As an organization that plays a role as an ASN management organizer, BKPSDM Mojokerto District launched a performance management innovation. Suhita (Performance Data Count Upload System) is a website-based e-performance innovation that is useful as a facility for ASN in Mojokerto Regency Government in conducting performance planning to performance evaluation in a transparent and accountable manner. This study aims to describe how Suhita e-performance innovation in BKPSDM Mojokerto Regency. This research uses descriptive research with a qualitative approach. The focus of the research uses the theory of innovation success factors according to Luky (2019). The results showed that e-performance innovation through the Suhita website has not run optimally. In human resource indicators, leaders play a key role in encouraging and directing innovation. In technology indicators, the website used has a fairly high complexity. In organizational indicators, the implementation of innovation has been planned, organized, moved and controlled. In behavioral indicators, BKPSDM Mojokerto Regency has not succeeded in fostering the perception of ease of use of Suhita innovation. On the user satisfaction indicator, performance management innovation through the Suhita website only provides satisfaction for some users with certain positions. In the net benefit indicator, the net benefits of implementing this innovation are felt more by users with the position of personnel manager and performance appraiser. The suggestions that can be given include: 1) provide training for the innovation management team, especially innovation operators, 2) hold socialization with the target of all Suhita innovation users, 3) periodic coaching and evaluation, 4) simplify the appearance and Suhita website.